Cullin 5 regulates Dab1 protein levels and neuron positioning during cortical development - Feng, Libing (Cold Spring Harbor Laboratory Press, 2007)
Many laminated regions of the mammalian brain develop by the migration of neuronal precursor cells, whose final positions are coordinated by signals from the secreted molecule Reelin. Early events in Reelin signaling have been identified, but the mechanism of signal down-regulation has been unclear. A possible source of negative feedback is the Reelin-induced degradation of the critical intracellular signaling component, Disabled-1 (Dab1). Here we show that degradation of Dab1 depends on Dab1 phosphorylation at specific tyrosine residues and on the E3 ubiquitin ligase component Cullin 5 (Cul5). Cul5 forms complexes with SOCS (suppressors of cytokine signaling) proteins, which bind to phosphorylated Dab1 and target it for degradation in tissue culture cells. Ablation of Cul5 in migrating neurons causes an accumulation of active Dab1 protein and a unique cortical layering defect, characterized by excess migration and buildup of neurons at the top of the cortical plate. The results implicate Cul5 and SOCS proteins in down-regulation of Dab1 in vivo and show that Cul5 plays an essential role in regulating neuron migrations during cortical development, possibly by opposing a promigratory effect of Dab1.